Improving Public Control Authorities of Citizens' SelfGoverning Bodies in the Field of Nature Protection in Uzbekistan (Texas Journal of Multidisciplinary Studies, 2023)
In this article, the issues of improving the powers of citizens' self-government bodies in the field of ecology to conduct public control, practical proposals for changes and additions to the legislation are expressed